Assessing the Importance of Nonlinearities in the Development of a Substructure Model for the Wind Turbine CAE Tool FAST: Preprint - Damiani, R.; Jonkman, J.; Robertson, A.; Song, H. (National Renewable Energy Laboratory (U.S.), 2013)
Design and analysis of wind turbines are performed using aero-servo-elastic tools that account for the nonlinear coupling between aerodynamics, controls, and structural response. The NREL-developed computer-aided engineering (CAE) tool FAST also resolves the hydrodynamics of fixed-bottom structures and floating platforms for offshore wind applications. This paper outlines the implementation of a structural-dynamics module (SubDyn) for offshore wind turbines with space-frame substructures into the current FAST framework, and focuses on the initial assessment of the importance of structural nonlinearities. Nonlinear effects include: large displacements, axial shortening due to bending, cross-sectional transverse shear effects, etc.